U.S. Vietnamese parents' trusted sources of information and preferences for intervention messaging about HPV vaccination: A mixed methods study - Milkie Vu; Carla J. Berg; Nhat-Ha T. Pham; Jasmin A. Tiro; Cam Escoffery; Bonnie Spring; Robert A. Bednarczyk; Danny Ta; Namratha R. Kandula (Elsevier, 2023)
Objective: Assess trusted sources of information, perceived message effectiveness, and preferred dissemination strategies regarding adolescent HPV vaccination among U.S. Vietnamese parents. Methods: Data came from an observational, explanatory sequential mixed-methods study with U.S. Vietnamese parents of adolescents (408 survey participants; 32 interview participants). Surveys and interviews were conducted in both Vietnamese and English. Mixed-methods data were integrated and analyzed for confirmation, expansion, or discordance. Results: Both quantitative and qualitative findings confirm high trust in HPV vaccination information from providers, government agencies, and cancer organizations. Messages perceived as effective emphasize vaccine safety, experts' endorsement, importance of vaccination prior to HPV exposure, and preventable cancers. Qualitative findings expanded quantitative results, demonstrating a desire for evidence-based information in the Vietnamese language and addressing cultural concerns (e.g., effectiveness or potential side effects specific to Vietnamese adolescents, whether parents should delay HPV vaccination for Vietnamese adolescents). Quantitative and qualitative findings were incongruent about whether parents would trust information about HPV vaccination that is disseminated via social media. Conclusion: We identified credible messengers, feasible strategies, and elements of impactful messages for interventions to increase adolescent HPV vaccination for U.S. Vietnamese. Innovation: We focus on a high-risk, underserved population and integrate mixed-methods design and analysis.